Le Corbusier : an atlas of modern landscapes - Cohen, Jean-Louis.; Le Corbusier, 1887-1965.; Pare, Richard; Museum of Modern Art (New York, N.Y.) (London : Thames & Hudson, 2013)
This volume examines Le Corbusier's relationship with the topographies of five continents, in essays by thirty of the formeost scholars of his work and with contemporary photographs by Richard Pare.
Contents note continued: New York City: United Nations Headquarters, 1946-47 -- New York City: An Elusive Presence at The Museum of Modern Art Jean-Louis Cohen -- Cambridge, Massachusetts: Carpenter Center for the Visual Arts, 1959-63 -- Asia -- En Route to/from India: In the Sky with Sketchbooks Enrique Ramirez -- Chandigarh: Landscaping a New Capital Maristella Casciato -- Ahmedabad, India: Four Buildings, 1951-57 -- Baghdad: A Sport City That Might Have Been Mina Marefat -- Tokyo: National Museum of Western Art, 1954-59.
Catalog of an exhibition held at Museum of Modern Art, New York, June 15-Sept. 23, 2013.
Includes bibliographical references and index.
ARC
Keywords: Le Corbusier, -- 1887-1965 -- Exhibitions; Le Corbusier, -- 1887-1965; Architecture; Exhibition catalogs